A new determination of the primordial helium abundance using the analyses of H ii region spectra from SDSS. Issue 2 (28th January 2021) - Kurichin, O A; Kislitsyn, P A; Klimenko, V V; Balashev, S A; Ivanchik, A V
ABSTRACT: The precision measurement of the primordial helium abundance Y p is a powerful probe of the early Universe. The most common way to determine Y p is the analyses of observations of metal-poor H ii regions found in blue compact dwarf galaxies. We present the spectroscopic sample of 100 H ii regions collected from the Sloan Digital Sky Survey. The final analysed sample consists of our sample and HeBCD data base from Izotov et al. (2007 ). We use a self-consistent procedure to determine physical conditions, current helium abundances, and metallicities of the H ii regions. From a regression to zero metallicity, we have obtained Y p = 0.2462 ± 0.0022, which is one of the most stringent constraints obtained with such methods up to date and is in a good agreement with the Planck result $Y_{\rm p}^{\it { Planck}} = 0.2471 ± 0.0003$ . Using the determined value of Y p and the primordial deuterium abundance taken from Particle Data Group (Zyla et al. 2020 ) we put a constraint on the effective number of neutrino species N eff = 2.95 ± 0.16, which is consistent with the Planck one N eff = 2.99 ± 0.17. Further increase of statistics potentially allows us to achieve Planck accuracy, which in turn will become a powerful tool for studying the self-consistency of the standard cosmological model and/or physics beyond.